Coupled cryoconite ecosystem structure–function relationships are revealed by comparing bacterial communities in alpine and Arctic glaciers. Issue 2 (5th February 2014) - Edwards, Arwyn; Mur, Luis A.J.; Girdwood, Susan E.; Anesio, Alexandre M.; Stibal, Marek; Rassner, Sara M.E.; Hell, Katherina; Pachebat, Justin A.; Post, Barbara; Bussell, Jennifer S.; Cameron, Simon J.S.; Griffith, Gareth Wyn; et al.
Abstract Cryoconite holes are known as foci of microbial diversity and activity on polar glacier surfaces, but are virtually unexplored microbial habitats in alpine regions. In addition, whether cryoconite community structure reflects ecosystem functionality is poorly understood. Terminal restriction fragment length polymorphism and Fourier transform infrared metabolite fingerprinting of cryoconite from glaciers in Austria, Greenland and Svalbard demonstrated cryoconite bacterial communities are closely correlated with cognate metabolite fingerprints. The influence of bacterial‐associated fatty acids and polysaccharides was inferred, underlining the importance of bacterial community structure in the properties of cryoconite. Thus, combined application of T‐RFLP and FT‐IR metabolite fingerprinting promises high throughput, and hence, rapid assessment of community structure–function relationships. Pyrosequencing revealed Proteobacteria were particularly abundant, with Cyanobacteria likely acting as ecosystem engineers in both alpine and Arctic cryoconite communities. However, despite these generalities, significant differences in bacterial community structures, compositions and metabolomes are found between alpine and Arctic cryoconite habitats, reflecting the impact of local and regional conditions on the challenges of thriving in glacial ecosystems.